Справочник кустаря: рецепты / Г. Г. Бродерсен ; [редактор В. Третьякова] - Бродерсен Густав Густавович (Русский дом, 1997)
Экземпляры: с/ф № 16 (20191007) / Инвентарный номер: 46756 / Цена: / Авт.знак: Б 88 / ГРНТИ: 64 / ББК: 37.2я2